Comprehensive Analysis of Differentially Expressed lncRNAs miRNAs and mRNA and Their ceRNA Network of Patients With Rare-Earth Pneumoconiosis - Shi, Xue-min; Bai, Yu-chao; Gao, Yan-rong; Bu, Ning; Song, Hai-yan; Huang, Li-hua; Zhao, Yu-hang; Wang, Su-hua (Frontiers in Genetics, 2021)
Rare earth pneumoconiosis(REP) is the main occupational disease of rare earth exposed workers and there is no specific treatment. In this study, we performed high-throughput sequencing on the plasma of nine REP to describe and analyze the expression profiles of long noncoding RNA(lncRNAs), miRNAs and mRNAs and investigate their regulatory networks. Our results identified a total of 125 lncRNAs, 4 miRNAs, and 82 mRNAs were differentially-expressed in the plasma of patients with REP. Furthermore, Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were used to analyze the differentially expressed non-coding RNAs(ncRNAs). We found the differential expression of ncRNAs are mainly related to the response of cells to stimulation, Hedgehog signaling pathway and so on. We also constructed lncRNA-miRNA-mRNA networks to further explore their underlying mechanism and possible relationships in REP.We found that in the competitive endogenous RNA (ceRNA) networks, lncRNA acts as a sponge of miRNA to regulate the target gene. The expression results were verified by qRT-PCR and the protein interaction networks of differentially-expressed genes were constructed via the STRING database. OncoLnc online platform was used to do the lung cancer survival analysis among the top five mRNAs analyzed by Protein-protein interaction(PPI) network analysis. We found miR-16-2-3p may used as biomarker for REP, because it is closely related to the occurrence and prognosis of REP through inflammatory reaction and in lung squamous cell carcinoma, its expression levels were positively correlated with the overall survival rate of patients.